Нові та рідкісні для України види роду Corpinus (Pers.: Fr.) Gray. 2. Представники секції Coprinus - Придюк, М.П. (Інститут ботаніки ім. М. Г. Холодного НАН України, 2007)
Публикуются сведения о находках трех новых (Coprinus echinosporus Buller, C. herinkii Pilбt et Svr и ek, C. lagopides P. Karst.) и двух редких (C. pseudoradiatus Kьhner et Joss. ex Watling, C. spilosporus Romagn.) для Украины представителей рода Coprinus (Pers.: Fr.) Gray. Для всех видов указывается информация об их распространении и особенностях биологии, а для новых в Украине — также диагнозы и рисунки. In the paper 3 new (Coprinus echinosporus Buller, C. herinkii Pilat et Svrcek, C. lagopides P. Karst.) and 2 rare (C. pseudoradiatus K .. hner et Joss. ex Watling, С spilosporus Romagn.) for Ukraine records of the genus Coprinus (Pers.: Fr.) Gray are reported. For all species information about their distribution and peculiarities of biology is presented, and for new in Ukraine ones diagnoses and drawings are also provided.